Study the Prevalence of Bacterial Conjunctivitis in Iraq - Alash, Sameer (Iraqi Journal of Science, 2025)
The study was done in the Hospital of Ibn-AL-Hythem for eyes infections in Baghdad from July till October of 2014. 120 conjunctiva eyes swap samples were collected from patients with pinkness or redness of the conjunctiva, which include 59 male and 61female. The diagnoses of specimens were done in the laboratories of the hospital by using the Analytical Profile Index System (API system). The results showed that 29(24.1%) samples were positive for bacterial infections while 91(75.9%) samples gave negative results, which mean conjunctivitis occurs by other causes. The study showed low in the percentage of bacterial infections that occurred in the eyes lid conjunctiva as well as in the per- orbital region. The predominant isolated species were Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermides, Streptoccus spp, respectively.